Kondisi Kesejahteraan Rumah Tangga Nelayan Di Gampong Padang Baru Kecamatan Susoh Kabupaten Aceh Barat Daya - Nabawi, Muhammad (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Fishermen are a community that is very dependent on existing marine resources. Apart from depending on marine resources, they also depend on natural conditions, fuel oil, education, skills and also the wealth they own, so that this can cause the income earned by fishermen to be less than optimal and automatically not optimal to meet their daily needs and making the welfare conditions of the household low. This research used descriptive qualitative research methods, the research subjects used purposive sampling techniques, the objects used were 17 people, namely the village head, village secretary, panglima laot, 7 fishing communities using fishing gear and fishing communities who cultivated fish and shrimp. Data collection techniques used were observation, interviews and documentation. Based on the results of interviews with fishermen in Gampong Padang Baru, Susoh District, Southwest Aceh Regency, it is stated that the condition of fishermen in realizing household prosperity in general is that fishermen are able to carry out various kinds of activities to create household welfare as seen from their income which is not enough. to meet existing needs. However, fishermen also look for side jobs, for example farming, casual labor and trading. The strategies used in this research are business alternative strategies, family members joining in the work, savings strategies, and networking strategies.